Investigation of side electromagnetic radiation generated during the operation of devices with sensory input of information - E. A. Rogozin; R. E. Rogozin; D. G. Silka; I. D. Korobkin; M. O. Meshcheryakov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. In order to determine the "security" of a special purpose informatization object, it is necessary to calculate the indicators of side electromagnetic radiation generated during the operation of devices with sensor input of information associated with information leakage through technical channels. It is also necessary to develop a list of actions to neutralize potential threats (including the development of an information protection system to protect against this type of threat).Method. The study of side electromagnetic radiation generated during the operation of devices with sensory input of information is carried out using expert documentary and instrumental methods.Result. The results of the study of side electromagnetic radiation generated during the operation of devices with sensor input of information are given and aspects of improving special measures for the protection of information at a special purpose informatization object are determined.Conclusion. The direction of this study is very relevant and requires further development of organizational and technical measures to implement the requirements of regulatory legal documents for the protection of information.